Pancytopenia in a newborn due to maternal piperacillin and human leukocyte antigen antibodies. (April 2022) - Li, Ping; Chen, Zengsheng; Wang, Rong; Shao, Changfeng; Liu, Yan; Ju, Qiang; Zong, Peng; Wang, Haiyan
Abstract: Background: Piperacillin antibody-induced immune hemolytic anemia is not rare in adults, and there have been reports of anti-HLA antibody-induced newborn platelet transfusion refractoriness. However, there has been no report of piperacillin-accompanied anti-HLA antibody-induced newborn pancytopenia. Case Report: We herein present the case of a newborn with pancytopenia from a mother who carried anti-HLA-B55, anti-HLA-DR11, and piperacillin antibodies. The newborn HLA genotypes were HLA*B55:02 and HLA*DRB1*11:01. IgG antibodies can be transferred to the newborn via the placenta and induce the destruction of the platelet and white blood cells, which carry the corresponding antigens. Piperacillin antibodies coupling with newborn red blood cells (RBCs) led to the destruction of the RBCs and hemolytic anemia. Results: The direct anti-globulin test was positive for RBCs in the newborn, and piperacillin antibodies were positive in both the newborn and his mother. Anti-HLA antibodies were positive in the maternal serum, whereas homologous antigens were positive in the newborn. The direct anti-globulin test of platelet was weekly positive in the newborn. Conclusion: Piperacillin and anti-HLA antibodies can pass through the placenta, induce incompatible blood cell destruction, and cause a series of clinical syndromes in newborns.